Perceptions concerning successful development of Finnish players involved in the National Football League (NFL) - Kuuttila, Karri Matti (2017)
Development of American Football in Finland is largely influenced by its licensed participants and Finland's American Football Union (Suomen Amerikkalaisen Jalkapallon Liitto, SAJL). To increase competitive excellence and the level of competition at national and international levels requires certain psychological skills in supportive environments, which later have to be turned into opportunities. Multiple large-scale studies (Bloom, 1985; Csikszentmihalyi, Rathunde, Whalen, & Wong, 1993) on talent development in a vast number of areas (art, music, sport, science), show that helping individuals enhance competence is not just hand picking talented people and introducing financial contributions. Turning talent into accomplishments involves the development of psychological skills, systems of habit, orientations, and the presence of supportive environments that nurture physical and mental development (Gould, Dieffenbach, & Moffett, 2001). The aim of this study was to examine the perceptions of Finnish NFL experienced athletes’ concerning their paths to success in American Football. Participants in this retrospective case study were five Finnish players, who had played in the NFL. Individual interviews questioned players about psychological characteristics, mentorship, and specialization. Results indicated that psychological development of talented athletes happened over a long period of time. Participants used a variety of psychological skills incorporated throughout their careers influenced by multiple people such as family members and coaches. Praise that was realistic, believable and punctual was found to have more effect on the athlete than praise that was meaningless, delayed, and did not stem from something specific. Psychological talent development was best seen as a system made up of many influences and factors that include not only important people to self, but also achievement strategies, balanced motivation, and dealing with the results. This long process, in regards to American football, requires a proper support system and is nurtured by encouragement and exposure to fun if success is to be achieved. By creating a psychological profile for the SAJL website, the importance of psychological skills, orientations, and habits may be further developed and understood within coaching, talented athletes, and the supporting networks around them.